A CMOS-Integrated Radar-Assisted Cognitive Sensing Platform for Seamless Human-Robot Interactions - Fang, Zhongyuan; Lou, Liheng; Tang, Kai; Wang, Wensong; Chen, Bo; Wang, Yisheng; Zheng, Yuanjin (IEEE International Symposium on Circuits and Systems proceedings, 2021)
With the rapid development of the internet of things (IoT), industry 4.0, smart manufacturing, intelligent building techniques, robots are becoming more and more demanding for emerging new applications. For robots used in complex environments, precise sensing of its surroundings is essential to enable safe and robust operation. Comprehensive and cognitive perception capability is needed to recognize human subjects in a complex and dynamic environment to avoid the possible collisions. Moreover, comprehensive sensing is required to enable accurate simultaneous localization and mapping (SLAM) under scenarios with clutters and moving human subjects. To achieve the goal, a CMOS-integrated radarassisted robot sensing platform is proposed. By leveraging the phased-array radar techniques and time-phase processing techniques, high accuracy can be achieved for localization and recognition of human subjects. Fabricated in a 65-nm CMOS process, the chip-scale radar sensing platform is with compact size. A series of experiments have been carried out on verifying the capabilities of the radar platform for ranging and human recognition based on vital signs, exploring the potential for seamless human-robot interaction applications.